EP204 Post irradiation primary osteosarcoma of the breast: a case report of an extremely rare entity. (1st November 2019) - Elghobashy, M; Bartlett, H; Rao, R; Deshmukh, N; Shaaban, AM
Abstract : Introduction/Background: Amongst the rarest of breast tumours is the non-epithelial primary mammary osteosarcoma, which has only been reported in ∼100 cases in the past 50 years. The differentials include matrix producing metaplastic carcinoma of the breast and malignant phyllodes tumour with osteosarcomatous differentiation. Methodology: This report describes an extremely rare case of primary osteosarcoma of the breast arising following radiotherapy for primary breast cancer. Results: A 73-year old female presented with a lump and pulling sensation at the upper outer quadrant of her right breast. She had a history of a 3 mm, grade 2, node negative invasive ductal carcinoma of the same breast 10 years prior to presentation, which was treated by wide local excision, axillary node sampling and radiotherapy. On examination, a fixed lump was identified at the lower quadrant of the right breast away from the wide local excision scar but in the field of radiotherapy. No abnormal axillary lymph nodes were found on imaging. A diagnostic excision was fully processed for histological examination and showed the lesion to be markedly calcified. A highly cellular malignant spindle cell lesion merged with an osteoid matrix and foci of calcification and bone formation was found. Immunohistochemistry was negative for a large panel of broad spectrum and basal cytokeratins as well as for S100, Melan A, CD34, SMA, Beta Catenin and Desmin. Due to the lack of epithelial/glandular differentiation, in situ carcinoma or leaf-like pattern, the diagnosis of malignant post irradiation osteosarcoma was made. Subsequent mastectomy revealed no residual disease. The patient remains well 7 months following diagnosis. Conclusion: Osteosarcoma following radiotherapy should be considered in the differential diagnosis of breast lesions showing malignant osteoid differentiation. Due to the rarity of the lesion, extensive sampling and careful search for epithelial differentiation including basal cytokeratin immunohistochemistry is required to guide management. Complete surgical excision is required. Disclosure: Nothing to disclose.